2021
DOI: 10.1007/s11095-021-03112-x
|View full text |Cite
|
Sign up to set email alerts
|

The pH Dependence of Niclosamide Solubility, Dissolution, and Morphology: Motivation for Potentially Universal Mucin-Penetrating Nasal and Throat Sprays for COVID19, its Variants and other Viral Infections

David Needham

Abstract: Motivation With the coronavirus pandemic still raging, prophylactic-nasal and early-treatment throat-sprays could help prevent infection and reduce viral load. Niclosamide has the potential to treat a broad-range of viral infections if local bioavailability is optimized as mucin-penetrating solutions that can reach the underlying epithelial cells. Experimental pH-dependence of supernatant concentrations and dissolution rates of niclosamide were measured in buffered solu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 55 publications
2
17
0
Order By: Relevance
“…It can be present in one of several anhydrous and hydrated polymorphs, each having different water solubilities, thereby affecting formulation and clinical utility (de Villiers et al 2004). Pure niclosamide has an intrinsic solubility of ~ 1-2 µM for its most stable monohydrate H B polymorph (Needham 2022;van Tonder et al 2004). Other intranasal formulations under current clinical testing (Backer et al 2021;Sommer et al 2021;Weiss et al 2021) have sought to increase the amount of niclosamide in solution by resorting to niclosamide ethanolamine (NE) that is slightly more soluble, but is generally more toxic, as a skin, eye, and respiratory irritant (AKSci 2022;Cayman-Chemicals 2019;DHSS 2002).…”
Section: Scientific Motivation Preformulation Drug Characterizationmentioning
confidence: 99%
See 3 more Smart Citations
“…It can be present in one of several anhydrous and hydrated polymorphs, each having different water solubilities, thereby affecting formulation and clinical utility (de Villiers et al 2004). Pure niclosamide has an intrinsic solubility of ~ 1-2 µM for its most stable monohydrate H B polymorph (Needham 2022;van Tonder et al 2004). Other intranasal formulations under current clinical testing (Backer et al 2021;Sommer et al 2021;Weiss et al 2021) have sought to increase the amount of niclosamide in solution by resorting to niclosamide ethanolamine (NE) that is slightly more soluble, but is generally more toxic, as a skin, eye, and respiratory irritant (AKSci 2022;Cayman-Chemicals 2019;DHSS 2002).…”
Section: Scientific Motivation Preformulation Drug Characterizationmentioning
confidence: 99%
“…Recognizing that niclosamide is a weak acid with a pKa ~ 7.12, the data in the earlier paper (Needham 2022) showed that excess pure, probably anhydrous (AK Sci), niclosamide could readily dissolve and equilibrate in aqueous buffered solution. Solubilities ranged from an intrinsic solubility of 2.53 µM at pH 3.66 to 30 µM a nasally safe pH 8.3, just by slightly increasing the alkalinity.…”
Section: Scientific Motivation Preformulation Drug Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Later in 2021, universal prophylactic nasal throat sprays as early treatments against SARS-CoV-2 and its more contagious variants were investigated. In particular, a low dose, prophylactic solution of niclosamide (20 μM) at a nasally safe and acceptable pH of 7.96, and a throat spray of up to 300 μM at pH 9.19 were proposed as the simplest and potentially the most effective formulations from both an efficacy as well as manufacturing and distribution standpoints, since no cold chain would be then required [ 168 ].…”
Section: Anthelmintic Drugs Against Sars-cov-2mentioning
confidence: 99%